Genome editing in mouse spermatogonial stem cell lines targeting the Tex15 gene using CRISPR/Cas9 - Yeşilbostan, Suheyla; Akkurt, Mustafa Yenal; Özkavukçu, Sinan; Kul, Oǧuz; Çınar, Bengi (Frontiers in Veterinary Science, 2025)
CRISPR/Cas9-mediated DNA endonuclease technology has been extensively utilized to introduce targeted genomic mutations for investigating biological processes across various cell types and organisms. In spermatogonial stem cells (SSCs), CRISPR/Cas9 has proven to be an effective tool for elucidating the genetic mechanisms underlying spermatogenesis and infertility. Additionally, it holds potential applications in disease prevention, transgenic animal production, and genetic improvement of livestock. This study aimed to optimize the lipid-based transfection of a lentiviral plasmid vector into SSCs by targeting the Tex15 gene, which is associated with infertility in humans, using CRISPR/Cas9. The efficiency of genome editing was assessed by detecting frameshift indel mutations starting from c.959C in exon 1 of the Tex15 gene using mutation site enzyme cut analysis, sanger sequencing, and in silico analyses. The highest transfection efficiency was achieved with a 1:3.5 DNA:DNAfectin ratio, which was identified as the optimal condition for SSC transfection. CRISPR-Cas9 editing in a monoclonal cell line derived from a single cell yielded high efficiency (model fit R = 0.97). Sequence analysis revealed two possible indel variants, indicating possible heterozygous biallelic editing within the same genome. Our findings demonstrate the potential of SSC-mediated genome editing for generating transgenic animals, enhancing productivity in livestock, and advancing novel therapeutic strategies for genetic disorders in animals and human male infertility.